Evaluating the Reading Section of English National Standardized School Exams (USBN): (A Field Study in SMK NU Ungaran) (Language Circle: Journal of Language and Literature, 2019)
With regard to the role of English in Indonesia that is mainly used for academic purpose, it is important to sharpen the two skills, reading and writing, more than the other two skills, listening and speaking. Based on that fact, this study focuses on reading skills, especially in reading comprehension skills. Reading comprehension skill is closely related to literacy levels that nowadays considered important by educational institution. The data was taken from reading comprehension questions in English USBN question sheet and the students’ answer sheets. The participants are students of XII grade of SMK NU Ungaran that are randomly chosen. The result of this study showed that Out of 50 students, 59% of them are best cope with editing task, followed by 56% in dealing with reading comprehension task, 50% of gap-filling task, 48% with short answer task and the least is 22% in vocabulary task. This meant that the proficiency level of reading comprehension of students in XII grade SMK NU Ungaran still needs to elevate. They were still lack in term of vocabulary and understanding the ideas implicitly delivered in the text.